Mathematics Anxiety: A Systematic Literature Review with Bibliometric Analysis - Novita Maulidya Jalal (Journal of Innovative and Creativity, 2025)
This study aims to analyze mathematics anxiety as a significant psychological phenomenon among students at various educational levels and cultures. Using a Systematic Literature Review (SLR) approach and bibliometric analysis, this study identifies research trends, causal factors, impacts, and intervention strategies related to mathematics anxiety. The results indicate that mathematics anxiety negatively impacts the quality of students' learning and career choices. There has been a significant increase in publications since 2010, especially from countries such as the United Kingdom and the United States, indicating that this issue is receiving increasing attention. Various factors, including the role of teachers and cultural context, contribute to the development of mathematics anxiety, while interventions such as collaborative learning and the use of digital technology are effective in reducing this anxiety. The conclusions of this study emphasize the importance of designing educational programs that are sensitive to students' psychological aspects, with the hope of improving the quality of mathematics education and supporting students in their learning process.